The use of remote sensing and Geographic Information Systems in Monitoring drought the Algerian steppe - Khenioui, Abderrezak; Boukhalfa, Salah; Bougherara, Ahmed (Technium Social Sciences Journal, 2023)
The present study aims to use remote sensing techniques and geographic information systems (GIS) in monitoring and detecting droughts in the steppe regions (Tiaret city as a model) during the period (2002-2022). In pursuit of this aim, some indicators were used, such as the surface temperature index (LST), soil moisture index (SMI), standardized difference vegetation index (NDVI), and aridity index (AI). Depending on the Terra satellite’s visuals, which are specialized in observing the earth and tracking changes that may occur in it. The purpose of the study is to demonstrate the extent to which the Algerian steppe regions, particularly the southern ones, are vulnerable to drought as a result of the climatic changes that the globe is experiencing in general. This is confirmed by the indicators that were used in this study (LST), (SMI), ( NDVI), (and AI), In addition to this, unregulated activities, such as grazing, unplanned reclamation, and others, have exacerbated the severity of the problem, and in order to safeguard this environment, it must be regularly monitored and protected.